2011
DOI: 10.1186/1472-684x-10-19
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude of final - year medical students in Germany towards palliative care - an interinstitutional questionnaire-based study

Abstract: BackgroundTo care for terminally ill and dying patients requires a thorough medical education, encompassing skills, knowledge, and attitudes in the field of palliative care. Undergraduate medical students in Germany will receive mandatory teaching in palliative care in the near future driven by recent changes in the Medical Licensure Act. Before new curricula can be implemented, the knowledge of medical students with respect to palliative care, their confidence to handle palliative care situations correctly, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
1
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 16 publications
8
71
1
13
Order By: Relevance
“…Die Palliativmedizin ist seit 2011/2012 integraler Bestandteil der ärztlichen Ausbildung (Querschnittfach 13 "Palliativ-und Schmerzmedizin"; [1,12,16]). Patienten mit lebenslimitierenden Erkrankungen im weit fortgeschrittenen Erkrankungsstadium werden zunehmend auch in der Regelversorgung betreut [1].…”
Section: Diskussionunclassified
See 2 more Smart Citations
“…Die Palliativmedizin ist seit 2011/2012 integraler Bestandteil der ärztlichen Ausbildung (Querschnittfach 13 "Palliativ-und Schmerzmedizin"; [1,12,16]). Patienten mit lebenslimitierenden Erkrankungen im weit fortgeschrittenen Erkrankungsstadium werden zunehmend auch in der Regelversorgung betreut [1].…”
Section: Diskussionunclassified
“…Die Behandlung von Palliativpatienten benötigt nach Aussagen mehrerer Autoren und der Expertenrunde besondere Kenntnisse und Ausbildungs-bzw. Weiterbildungsinhalte [1,16]. In diesem Zusammenhang stellt sich jedoch die Frage, ob die palliativmedizinisch orientierte Behandlung und deren Inhalte lediglich Patienten am Lebensende bzw.…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…The Collet Lester Fear of Death and Dying Scale-Revised [23][24][25] was used to obtain information about attitudes towards and fears of death and dying of self and others. Data about participants' palliative care knowledge was collected by means of the Three Step Questionnaire [6,7], an instrument consisting of 21 questions related to eight case examples.…”
Section: Questionnairesmentioning
confidence: 99%
“…A current survey conducted in 2012 to investigate the progress of implementation of palliative care curricula in medical faculties in Germany [6,7] demonstrated that UPCE was mainly taught interprofessionally and in an advanced semester and comprised twelve to forty-three TU.…”
Section: Introductionmentioning
confidence: 99%